Smart Health Tracker: Arduino-Powered Automatic Height and Weight Measurement with Web Integration - Kuswanto, Dwi (Universitas Trunojoyo Madura, 2024)
The golden age in toddlers significantly influenced their growth, so it was essential to know the adequacy of nutritional needs in children. One way to assess the adequacy of nutrition in children was by measuring height and weight. However, height and weight variables in toddlers were highly representative. Until now, both measurement processes have been done manually, and the results have been recorded in a logbook. Thus increasing the risk of errors due to human involvement in data recording. This research aimed to design a prototype of an automatic device capable of measuring height and weight automatically. This prototype was based on Arduino Uno technology using ultrasonic sensors along with weight sensors, such as load cells and HX711. Furthermore, the data generated were integrated with the web for more effective storage. From the designed device, a pretty good level of measurement accuracy was obtained. The test results showed that the height-measuring device using ultrasonic sensors demonstrated an accuracy level of 97.99%. Meanwhile, the weight-measuring device using a load cell sensor showed an accuracy level of 82.53%. After testing together with the Melati Putih Posyandu Cadres, a good response was obtained. The satisfaction level measurement using the System Usability Scale method yielded a score of 80.75 points. It can be concluded that the built system was in the acceptable category.